Development and Validation of a Multiplex Non-HLA Antibody Assay for the Screening of Kidney Transplant Recipients - Kamburova, Elena G.; Kardol-Hoefnagel, Tineke; Wisse, Bram W.; Joosten, Irma; Allebes, Wil A.; van der Meer, Arnold; Hilbrands, Luuk B.; Baas, Marije C.; Spierings, Eric; Hack, Cornelis E.; van Reekum, Franka E.; van Zuilen, Arjan D.; et al. (Frontiers in Immunology, 2018)
The best treatment for patients with end-stage renal disease is kidney transplantation. Although graft survival rates have improved in the last decades, patients still may lose their grafts partly due to the detrimental effects of donor-specific antibodies (DSA) against human leukocyte antigens (HLA) and to a lesser extent also by antibodies directed against non-HLA antigens expressed on the donor endothelium. Assays to detect anti-HLA antibodies are already in use for many years and have been proven useful for transplant risk stratification. Currently, there is a need for assays to additionally detect multiple non-HLA antibodies simultaneously in order to study their clinical relevance in solid organ transplantation. This study describes the development, technical details and validation of a high-throughput multiplex assay for the detection of antibodies against 14 non-HLA antigens coupled directly to MagPlex microspheres or indirectly via a HaloTag. The non-HLA antigens have been selected based on a literature search in patients with kidney disease or following transplantation. Due to the flexibility of the assay, this approach can be used to include alternative antigens and can also be used for screening of other organ transplant recipients, such as heart and lung.